2011
DOI: 10.1074/jbc.m110.192062
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Storage of Dermatan Sulfate in Sanfilippo Disease

Abstract: Mucopolysaccharidoses are a group of genetically inherited disorders that result from the defective activity of lysosomal enzymes involved in glycosaminoglycan catabolism, causing their intralysosomal accumulation. Sanfilippo disease describes a subset of mucopolysaccharidoses resulting from defects in heparan sulfate catabolism. Sanfilippo disorders cause severe neuropathology in affected children. The reason for such extensive central nervous system dysfunction is unresolved, but it may be associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 42 publications
2
37
0
2
Order By: Relevance
“…Chondroitin/dermatan sulfate was low in all tissues and did not accumulate except for a twofold increase in the liver of the knockouts (Fig. 2H), which may reflect secondary storage induced by heparan sulfate accumulation, as reported for fibroblasts derived from MPS IIIA, IIIB, IIIC, and IIID patients (11).…”
Section: Arsg-deficient Mice Show Lysosomal Storage and Cellular Altementioning
confidence: 83%
“…Chondroitin/dermatan sulfate was low in all tissues and did not accumulate except for a twofold increase in the liver of the knockouts (Fig. 2H), which may reflect secondary storage induced by heparan sulfate accumulation, as reported for fibroblasts derived from MPS IIIA, IIIB, IIIC, and IIID patients (11).…”
Section: Arsg-deficient Mice Show Lysosomal Storage and Cellular Altementioning
confidence: 83%
“…Urinary CS excretion has been studied semiquantitatively in studies on the DS:CS ratio as potential biomarkers, but no absolute levels have been reported [21]. Secondary accumulation of metabolites other than the primary storage material has been reported in several lysosomal storage disorders, and include GAGs and complex lipids [39,40]. In these studies general lysosomal dysfunction and direct effect of storage material on activity of some other lysosomal enzymes have been proposed as underlying mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…We do not know whether severe cardiac involvement in MPS III-A is rare or simply underdiagnosed. However, the finding that MPS III is also associated with secondary storage of dermatan sulfate [18] suggests that other organs, in addition to those of the nervous central system, can be severely affected by this disorder. Furthermore, the rapidly lethal course of cardiomyopathy may hinder diagnostic investigation of MPS in affected patients.…”
Section: Discussionmentioning
confidence: 99%